2017
DOI: 10.1038/bjc.2017.252
|View full text |Cite
|
Sign up to set email alerts
|

GEIS-21: a multicentric phase II study of intensive chemotherapy including gemcitabine and docetaxel for the treatment of Ewing sarcoma of children and adults: a report from the Spanish sarcoma group (GEIS)

Abstract: Background:First Spanish trial of Ewing sarcoma (ES) including adults and children with the aim to test the efficacy of Gemcitabine and Docetaxel (G/D) in newly diagnosed high-risk (HR) patients.Methods:This was a prospective, multicentric, non-randomised, open study for patients ⩽40 years with newly diagnosed ES. HR patients (metastatic, axial-pelvic primaries or bone marrow micrometastasis) received 2 window cycles of G/D. Patients with an objective response (OR) to G/D received 12 monthly cycles of G/D afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The same results were achieved for maximum tumor diameter, tumor type, brain invasion, and bone invasion. However, a recent study has reported that age was an independent prognostic factor for the prognosis of patients (12).…”
Section: Discussionmentioning
confidence: 99%
“…The same results were achieved for maximum tumor diameter, tumor type, brain invasion, and bone invasion. However, a recent study has reported that age was an independent prognostic factor for the prognosis of patients (12).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently occurring are Ewing sarcoma, osteosarcoma, and rhabdomyosarcoma, altogether representing 13% of all malignant tumors in patients younger than 14 years, and up to 18% of all tumors among patients between 15 and 19 years [2][3][4]. With up-to-date treatment modalities, the 5-year survival rates have improved in the last decade to 79% for Ewing sarcoma, 73% for osteosarcoma, and 70% for rhabdomyosarcoma [5][6][7]. Unfortunately, intensive and multimodal treatments currently used in pediatric sarcomas have topped their efficacy [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, in prospective multi‐institutional trials for relapsed Ewing sarcoma, the response rate for 80 total patients was only 12% 8,9 . In the one study involving newly diagnosed patients with Ewing sarcoma, two cycles of GEM/DOC were used as an upfront window to treat 17 evaluable higher‐risk patients 10 . Although 41% of patients had a partial response, 29% experienced progression during this window.…”
Section: Introductionmentioning
confidence: 99%